Impact of hospital care volume on clinical outcomes of laparoscopic radical hysterectomy for cervical cancer: A systematic review and meta-analysis - Lee, Banghyun (Medicine (Baltimore), 2018)
BACKGROUND: In cervical cancer, the impact of hospital volume of laparoscopic radical hysterectomy (LRH) has not been investigated systematically as in ovarian cancer. The aim of this study was to investigate the impact of hospital care volume of LRH on treatment outcomes of patients with cervical cancer. METHODS: The PubMed, Embase, and Cochrane Library databases were searched with the terms “cervical cancer,” “radical hysterectomy,” and “laparoscopy.” The selection criteria included studies presenting operative outcomes and/or perioperative complications of LRH from high-volume hospitals (HVHs) (≥15 cases/year) and low-volume hospitals (LVHs) (<15 cases/year). Fifty-nine studies including 4367 cases were selected. Linear regression analysis weighted by the average annual case number in each study was performed to evaluate differences between the groups. RESULTS: In HVH, a higher number of lymph nodes (24.5 vs 21.1; P = .037) were retrieved by LRH in older women (48.4 vs 44.5 years; P = .010) with tendencies of shorter operation time (224.4 vs 256.4 minutes; P = .096) and less blood loss (253.1 vs 322.2 mL; P = .080). Compared with LVH, HVH had fewer patients with stage IA disease (13.8 vs 24.4%; P = .003) and more patients with stage IIA disease (15.3 vs 7.1%; P = .052) with comparable 5-year overall survival (93.1 vs 88.6%; P = .112). CONCLUSION: HVH is a prognostic factor for operative outcome and perioperative complications in patients with cervical cancer undergoing LRH. The exact effect of hospital volume on survival outcome needs to be evaluated.